Power and Thermal Management Issues for Portable Processors - Diary R. Sulaiman (Zanco Journal of Pure and Applied Sciences, 2020)
The advancement of modern CMOS technology scaling causes an exponential rise of system's power dissipation and temperatures in submicron technology node, which growth production and operating costs. Thermal energy and generated heat are becoming a prominent major issue in the context of portable applications (telephony, PDAs, digital cameras ...) and must be considered at each design level. The performance of portable processors is critically affected by dissipated power and operational temperature. The designers are forced to design a proper cooling system, especially heatsinks which consistently allows a low power and low temperature regulation of high-speed processors. In this article, several different heatsinks are modeled, tested, and designed to optimize the microprocessor’s cooling system while ensuring proper thermal operation and lowest power dissipation. The proposed adopted heatsink and their selected design configurable parameters are analyzed theoretically for different validations conditions and operation modes in various real-time thermal conditions. Thermal Analysis Package is used for simulation the proposed heatsinks model. Results shows the specification improvements of the design model for ensuring power required to cool in time of 0.851 W, time to cool by 15s, and heat to remove is 12.77J which confirms theoretical fundamentals and sufficient improvement of temperature minimization and better performance of the cooling system was achieved.